Conversations avec Lilian Thuram - Salim Lamrani (Études Caribéennes)
With honorary doctorates in humanities from the University of Stockholm (Sweden) and the University of Stirling (Scotland), Lilian Thuram set up the Education Against Racism Foundation in 2008 to raise awareness in French society, and particularly among young people, of the realities of discrimination against the most vulnerable groups. A prolific author, his books include Mes étoiles noires, Manifeste pour l'égalité, Notre histoire and La pensée blanche. He was awarded the Prix de l'éthique by the Kéba-Mbaye Foundation in Senegal for his work.In these conversations, Lilian Thuram explains what "white thinking" is, evokes the reality of discrimination, analyzes the roots of racist discourse and calls for education against this scourge in order to rid society of prejudices linked to skin color.